Assessment of the Common Risk Factors Associated with Type 2 Diabetes Mellitus in Jeddah - Manal A. Murad; Samia S. Abdulmageed; Rahila Iftikhar; Bayan Khaled Sagga (International Journal of Endocrinology)
Risk factor management is important in avoiding life-threatening complications and preventing new-onset diabetes. We performed a case-control study in 2013 at ten primary health care centers in Jeddah, Saudi Arabia to determine the common risk factors of diabetes mellitus type 2 (DM2) and the demographic background of adult Saudi patients with DM2. Known diabetic patients were recruited as cases, while nondiabetic attendants were selected as controls. A pretested designed questionnaire was used to collect data from 159 cases and 128 controls. Cases were more likely than controls to be men (P<0.0001), less educated (P<0.0001), natives of eastern Saudi Arabia (P<0.0001), retired (P<0.0001), lower-salaried (P<0.0001), or married or divorced (P<0.0001). By univariate analysis cases were likely to be current smokers (P<0.0001), hypertensive (P<0.0001), or overweight/obese (P<0.0001). Cases were also more likely to have a history of DM in a first-degree relative (P=0.020). By multivariate analysis, cases were more likely to be older than 40 years (P<0.0001), less educated (P=0.05), married or divorced (P=0.04), jobless/housewives (P<0.0001), or current smokers (P=0.002). They were also more likely to have salaries <7000 Saudi riyals (P=0.01). Overall, prediabetic and high risk groups should be identified and counseled early before the occurrence of diabetes.